2008
DOI: 10.1111/j.1462-2920.2008.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

6‐Oxocyclohex‐1‐ene‐1‐carbonyl‐coenzyme A hydrolases from obligately anaerobic bacteria: characterization and identification of its gene as a functional marker for aromatic compounds degrading anaerobes

Abstract: In anaerobic bacteria, most aromatic growth substrates are channelled into the benzoyl-coenzyme A (CoA) degradation pathway where the aromatic ring is dearomatized and cleaved into an aliphatic thiol ester. The initial step of this pathway is catalysed by dearomatizing benzoyl-CoA reductases yielding the two electron-reduction product, cyclohexa-1,5-diene-1-carbonyl-CoA, to which water is subsequently added by a hydratase. The next two steps have so far only been studied in facultative anaerobes and comprise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
100
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 43 publications
2
100
0
2
Order By: Relevance
“…Recently, the characterization of the ring-opening hydrolases from G. metallireducens (BamA) and S. aciditrophicus (BamA Syn ) as well as the BamQ dehydrogenase from G. metallireducens further confirmed that the Thauera-type ␤-oxidation pathway is present in both facultative and obligate anaerobes ( Fig. 2) (206). The observation that the Rhodopseudomonas type is restricted to photosynthetic anaerobes may reflect an evolutionary adaptation of phototrophs to carry out the catabolism of aromatic and alicyclic acids through the same ␤-oxidation pathway (see below).…”
Section: Benzoate Catabolism: the Benzoyl-coa Degradation Pathwaymentioning
confidence: 82%
See 3 more Smart Citations
“…Recently, the characterization of the ring-opening hydrolases from G. metallireducens (BamA) and S. aciditrophicus (BamA Syn ) as well as the BamQ dehydrogenase from G. metallireducens further confirmed that the Thauera-type ␤-oxidation pathway is present in both facultative and obligate anaerobes ( Fig. 2) (206). The observation that the Rhodopseudomonas type is restricted to photosynthetic anaerobes may reflect an evolutionary adaptation of phototrophs to carry out the catabolism of aromatic and alicyclic acids through the same ␤-oxidation pathway (see below).…”
Section: Benzoate Catabolism: the Benzoyl-coa Degradation Pathwaymentioning
confidence: 82%
“…Sequence comparison analyses of the dienoyl-CoA hydratases and ring-opening hydrolases suggested the existence of two phylogenetic groups, one including the enzymes from T. aromatica and G. metallireducens and the deduced gene products from Magnetospirillum strains and a second group that includes the enzymes from S. aciditrophicus, the deduced gene products from Azoarcus species, and the hydrolase from the sulfate-reducing bacterium D. multivorans (206,279). This observation suggests that these two groups represent neither the phylogenetic relationship nor a common overall energy metab-olism of the organisms (facultative versus obligate anaerobes) but rather points to the fact that they might have been acquired by the corresponding bacteria through horizontal gene transfer events (206,279).…”
Section: Benzoate Catabolism: the Benzoyl-coa Degradation Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Following these results, three primer pairs were tested to detect genes involved in degradation of monoaromatic hydrocarbons. The primer pairs used were bssA_f/bssA_r to detect the bssA gene (Botton et al, 2007), BamA-SP9/BamA-ASP1 to detect the bamA gene (Kuntze et al, 2008) and bzAQ4R/ bzAQ4R to detect the bcrA gene (Song & Ward, 2005). With these primer pairs, however, no PCR product was obtained from the genomic DNA of strain sk43H T (Thauera aromatica K172 T was used as a positive control and fragments of the expected sizes were obtained in all cases).…”
mentioning
confidence: 99%